Comparative report of compliance to precautionary measures against COVID-19 in Nigeria and Jordan. Issue 8 (August 2021) - Al-Shattarat, Basiem; Amuda, Yusuff Jelili
Abstract: Purpose of the study: The purpose of this study is to comparatively report the strategies for implementation of safety measures against the transmission of Covid-19 in Nigeria as the heart of Africa and Jordan as the nexus of Arab world. Methodology: The methodology used in this study is systematic literature review (SLR) and content analysis of report of the secondary data on Covid-19 which was obtained from Nigerian Centre for Disease Control & Presidential Task Force in Nigeria and Jordanian National Committee for Epidemic. Main findings: The report showed indicators of compliance to precautionary measures against the spread of Covid-19 in both Nigeria and Jordan. There was an imposition total lockdown in major citizens like Lagos & Abuja in Nigeria and Irbid in Jordan while partial lockdown in other parts of the countries. Also, both countries tried to comply with the safety measures provided by World Health Organization (WHO) against Covid-19 such as: the use of facemask, social distancing, hand sanitizers and school activities were suspended. However, there is no specific fine against the violators of precautionary measures in Nigeria as compared to what is obtainable in Jordan where fines of Jordanian Dinars of 20–50 was imposed. Applications of this study: The report can be useful to Nigeria Centre for Disease Control & Presidential Task Force in Nigeria, Jordanian National Committee for Epidemic, health workers and policymakers towards strengthening compliance with safety measures that are put in place in curtailing further transmission of the virus. Novelty/originality of this study: Most studies on Covid-19 assessed the rate of the spread of the pandemic but this study attempts to comparatively examine the compliance of precautionary measures in combatting the spread of Covid-19 in both Nigeria and Jordan. The readers would benefit from the study by galvanizing efforts in ensuring the compliance to the safety measures against the transmission of Covid-19 in both Nigeria and Jordan. Abstract : Covid-19; Precautionary Measure; Nigeria Centre for Disease Control; Jordanian National Committee for Epidemic; Coronavirus Preparedness Group (CPG).